2019
DOI: 10.1002/jcb.29475
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs expression profiles in plasma exosomes from early‐stage lung adenocarcinoma and the potential biomarkers

Abstract: This study aimed to identify differential circular RNA (circRNA) in the plasma exosomes of patients with lung adenocarcinoma (LUAD) using high-throughput sequencing. First, exosomes were isolated using an exosome isolation kit and confirmed by Western blotting, transmission electron microscopy, and NanoSight Assay. Subsequently, plasma circRNA expression profiles were screened by high-throughput sequencing and confirmed by fluorescence quantitative real-time polymerase chain reaction (qRT-PCR) and Sanger seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 29 publications
1
41
0
Order By: Relevance
“…Exosomal miR-1247-3p induced cancer-associated fibroblast activation to foster lung metastasis of liver cancer [37], while exosome-transmitted lncARSR promoted sunitinib resistance in renal cancer [5], and exosomal circRNAs were found to promote the progression of hepatocellular carcinoma [38]. Circular RNAs in plasma exosomes of lung cancer have also been reported [39]. However, studies of exosomal circRNAs in NSCLC have not been performed to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomal miR-1247-3p induced cancer-associated fibroblast activation to foster lung metastasis of liver cancer [37], while exosome-transmitted lncARSR promoted sunitinib resistance in renal cancer [5], and exosomal circRNAs were found to promote the progression of hepatocellular carcinoma [38]. Circular RNAs in plasma exosomes of lung cancer have also been reported [39]. However, studies of exosomal circRNAs in NSCLC have not been performed to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have reported the construction of circRNA-miRNA-mRNA regulatory networks in LUAD [17,18], the current understanding of circRNA-related ceRNA networks in LUAD is limited, and further study is needed. In this study, we identi ed a potential circRNA-miRNA-mRNA ceRNA regulatory network in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, 182 exosomal circRNAs were reported to be differentially expressed in the plasma from LUAD patients compared with healthy controls. 160 These circulating exosomal circRNAs held great promise as non-invasive biomarkers in lung cancer. The levels of 22 circRNAs were altered in serum exosomes from patients with papillary thyroid carcinoma relative to healthy controls by high-throughput sequencing analysis.…”
Section: Main Textmentioning
confidence: 99%